2007
DOI: 10.1248/bpb.30.502
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Small Molecule Inhibitors of Cystic Fibrosis Transmembrane Conductance Regulator Protein: In Vitro and in Vivo Studies

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) protein is a cAMP-regulated chloride channel that has been proposed as a pharmacological target to reduce intestinal fluid loss in cholera. The aim of this study was to identify new CFTR inhibitors by high-throughput screening. Screening of 50,000 drug-like small molecules was performed using a cell-based assay of iodide influx in Fisher rat thyroid (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…CaCC has been found in the small intestine as well as in T84 cells . Several CFTR inhibitors, such as glibenclamide, 5-nitro-2-(3-phenylpropylamino)-benzoic acid, GlyH-101, and 2-[N-(3-hydroxy-4-carboxyphenyl)amino]-4-(4-methylphenyl)-thiazole (INH 1), have also been found to inhibit CaCC (McCarty et al, 1993;Rabe et al, 1995;Dawson et al, 1999;Muanprasat et al, 2004Muanprasat et al, , 2007. Therefore, to determine its target specificity, dihydroisosteviol was tested in T84 cells as a blocker of Ca 2ϩ -induced Cl Ϫ secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CaCC has been found in the small intestine as well as in T84 cells . Several CFTR inhibitors, such as glibenclamide, 5-nitro-2-(3-phenylpropylamino)-benzoic acid, GlyH-101, and 2-[N-(3-hydroxy-4-carboxyphenyl)amino]-4-(4-methylphenyl)-thiazole (INH 1), have also been found to inhibit CaCC (McCarty et al, 1993;Rabe et al, 1995;Dawson et al, 1999;Muanprasat et al, 2004Muanprasat et al, , 2007. Therefore, to determine its target specificity, dihydroisosteviol was tested in T84 cells as a blocker of Ca 2ϩ -induced Cl Ϫ secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several efforts have been made to search for promising drugs that could be used to treat cholera more efficiently. These methods include inhibitors of cholera toxin receptor binding (Pickens et al, 2004), 5-hydroxytryptamine receptor antagonists (Mourad et al, 1995;Turvill and Farthing, 1997), somatostatin receptor agonists (Farthing, 1996), enkephalinase inhibitors (Cézard et al, 2001), and CFTR inhibitors (Muanprasat et al, 2004(Muanprasat et al, , 2007. Several natural products isolated from plants have also been used as sources of pharmaceuticals and as ingredients of traditional medicines (Phillipson, 1994).…”
mentioning
confidence: 99%
“…In light of the results from dose-inhibition studies in T84 and MDCK cells, ISLQ is less potent than other CFTR inhibitors identified to date (12,28,31,32). However, the potential for therapeutic applications of ISLQ should not be underrated, as ISLQ also has other biological activities that, in conjunction with its inhibitory effect on CFTR, may be of added benefit in the treatment of cholera and/or PKD.…”
Section: CLmentioning
confidence: 99%
“…17) This cell model has been extensively employed to identify novel CFTR modulators and to characterize their mechanisms of action. [18][19][20][21] To our surprise, apical Cl − current analysis of FRT-CFTR cell monolayers demonstrated that DHIS had no effect on CFTR-mediated Cl − transport. This result led us to speculate that the inhibition of CFTR-mediated Cl − current by DHIS in T84 cells is not due to the direct effect on CFTR, but rather a result of action on other proteins that regulate CFTR function.…”
Section: Discussionmentioning
confidence: 91%